Analisis Daya Saing Strategi pada Terminal Petikemas Makassar dan Terminal Petikemas Bitung - Resty Yosna Panimba; Abdul Rahman Kadir; Andi Nur Baumassepe (Hasanuddin Journal of Business Strategy, 2019)
Increasing the flow of logistics in the digitalization era should be an opportunity for the port segment to increase its competitiveness at the world level. This study aims to describe and analyze the affecting factors of increasing competitive advantage at Makassar Container Terminal and Bitung Container Terminal and to determine the right strategy of Makassar Container Terminal and Bitung Container Terminal.This research was designed to direct strategic decisions depends on internal and external environment of both ports to improved their competitiveness. Decision of managerial strategic in this research was in the scope of SWOT, QSPM and Miles & Snow Typology. Location or place of research in Makassar and Bitung Container Terminal. The data collected includes secondary data. The population and sample in this study include Management of Makassar and Bitung Container Terminal as many as 40 people. Data analysis techniques use the RBV and Model I/O approach, TOWS analyze, QSPM and Miles & Snow Tipology.The result of this research showed that based by description of environment factors then Makassar Container Terminal in a position where threat that it was faced bigger so that it need to maximize existing strength while Bitung Container Terminal in a favorable position with the potential of adequate resources so that it was needed a aggressive strategy to increase its competitive advantage. Based on the Miles and Snow analysis that used, Makassar Container Terminal can apply defender strategy and Bitung Container Terminal can apply prospector strategy.